The immunoproteasome regulates ILC2 responses by modulating mitochondrial capacity - Paôline Laurent; Vidyanath Chaudhary; Daqiang Li; Marie Dominique Ah Kioon; Chen Zhang; William H. Miller; Hua Liao; Gang Lin; Carl F. Nathan; Franck J. Barrat (Proceedings of the National Academy of Sciences, 2025)
Type 2 innate lymphoid cells (ILC2s) contribute to type 2 immunity but have also been associated with multiple inflammatory diseases, including airway inflammation and asthma. We report that beyond its function of degrading poly-ubiquitinylated proteins, the immunoproteasome (i-20S) is required for the proper function of ILC2s by controlling their mitochondrial capacity. We found that 90% of the catalytic β subunits of proteasomes in human ILC2s (hILC2s) are the immuno- (β5i) rather than constitutive (β5c) isoform. Specific, noncovalent, reversible inhibition of i-20S β5i (LMP7) in hILC2s induced ROS production, which inhibited aconitase, leading to altered mitochondrial function and reduced levels of ATP. Reprogramming of metabolic status by an LMP7 inhibitor impaired ILC2 activation, without significant cytotoxicity or preventing their recovery. Hence, the selective inhibition of i-20S in ILC2 cells did not kill them but reversibly depleted their ATP, preventing their activation and cytokine secretion. In mice, proteasome inhibition similarly blocked mitochondrial function and ILC2 activation, preventing airway inflammation in response to IL33 and asthma in response to house dust mites. These findings reveal a previously unappreciated linkage between proteasome blockade, central carbon metabolism, and mitochondrial function and identify a strategy to regulate immune cell metabolism in inflammatory diseases.